2010
DOI: 10.1002/jbmr.223
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K inhibitors prevent bone loss in estrogen-deficient rabbits

Abstract: Two cathepsin K inhibitors (CatKIs) were compared with alendronate (ALN) for their effects on bone resorption and formation in ovariectomized (OVX) rabbits. The OVX model was validated by demonstrating significant loss (9.8% to 12.8%) in lumbar vertebral bone mineral density (LV BMD) in rabbits at 13-weeks after surgery, which was prevented by estrogen or ALN. A potent CatKI, L-006235 (L-235), dosed at 10 mg/kg per day for 27 weeks, significantly decreased LV BMD loss ( p < .01) versus OVX-vehicle control. ALN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 38 publications
8
115
1
Order By: Relevance
“…ALN treatment was previously observed to function as an antiresorptive leading to a BMD higher than that in the vehicle-treated group. 12 In this study, ALN treatment resulted in a frequency of collagen fibril observations intermediate between Sham and OVX values, although the differences in proportions of fibrils in Parallel and Oblique regions in these treatments were not significant. The bone resorption inhibitor CatKI also gave intermediate values for the frequency of collagen fibril observations and showed even less shift from the initial Sham values, with none of the comparisons versus other treatments being significant.…”
Section: Resultscontrasting
confidence: 50%
See 4 more Smart Citations
“…ALN treatment was previously observed to function as an antiresorptive leading to a BMD higher than that in the vehicle-treated group. 12 In this study, ALN treatment resulted in a frequency of collagen fibril observations intermediate between Sham and OVX values, although the differences in proportions of fibrils in Parallel and Oblique regions in these treatments were not significant. The bone resorption inhibitor CatKI also gave intermediate values for the frequency of collagen fibril observations and showed even less shift from the initial Sham values, with none of the comparisons versus other treatments being significant.…”
Section: Resultscontrasting
confidence: 50%
“…8,9 Discussion OVX is a common model used to study the effects of estrogen depletion. 8,9,[15][16][17] Pennypacker et al 12 applied the OVX model to study osteopenia in rabbits using the samples described herein and demonstrated osteoclastic bone resorption resulting from estrogen depletion. On the basis of the strong positive correlations between the experimental strength parameters and the tissue bone mineral content from animals from the same study, it was demonstrated that there were no obvious treatment-related changes in the material properties of vertebrae and femurs in the OVX rabbits treated with odanacatib or ALN for 27 weeks.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations